Respuestas

2014-02-21T06:38:54+01:00
En (1)                                                                      x=8
x-y+z=6.........x=6+y-z                                             y=7/2
en (2)                                                                      z=3/2
x+2y-5z=3....... 6+y-z+2y-5z=3
                        y=3z-1
en (3)
-x+3y-2z=1........... -(6+y-z)+3y-2z=1
                             z-6-y+3y-2z=1
                              2y-z=7
                               2(3z-1)-z=7
                               6z-2-z=7
                                 z=3/2

ahora solo remplazas el las ecuaciones originales